A critical study of the integrated school health policy and social determinants of health - Mofokeng, Neo Thabisile (University of the Witwatersrand, Johannesburg, 2024)
The Social Determinants of Health constitute a foundational concept in population health, playing a crucial role in achieving overall public health and addressing health inequalities. Moreover, the phenomenon of the Social Determinants of Health is essential for the development and management of policies. This study aims to conduct a qualitative retrospective policy analysis of the South African Integrated School Health Policy to assess whether the policy contents and imperatives align with the Social Determinants of Health. Furthermore, the study aims to explore the role of academics in shaping the Integrated School Health Policy, specifically focusing on their understanding of the Social Determinants of Health and the associated structural factors that underpin compromised health in school-going children. The data for this study was gathered through semi-structured interviews conducted with academics, who have direct experience in the policy process of school health policies. The secondary method of data collection included document analyses. Central to the findings is the realisation that the policy process of the Integrated School Health Policy encompassed the amalgamation of policy decisions and agenda-setting. It is a complex process which makes the identifying of decision-making protocols challenging and emphasises the impact of stakeholders' perspectives. The data presented advances the notion that the change in political norms and political will emerge as the critical drivers for the policy challenges associated with the Integrated School Health Policy. Notably, there was a lack of a systematic approach to addressing the Social Determinants of Health and providing comprehensive school health services. The study’s findings provide a basis for promoting evidence-based policies concerning school health services and examining ways to establish a health-ecosystem within an educational system. This approach not only benefits school-going children and individuals within the educational system, but also holds potential benefits for individuals residing in the communities located within the educational system.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; HEALTH EQUITY; THE SOCIAL DETERMINANTS OF HEALTH; HEALTH POLICY; SCHOOL HEALTH; HEALTH PROMOTING SCHOOLS; SDG-3: Good health and well-being